Comparative Study on the Rearing Performance of Muga Silkworm - K Neog; P Dutta; A Changmai; D Goswami; B Choudhury (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2015)
Muga silkworm, Antheraea assamensis Helfer, generally reared outdoor on standing host trees for which it is always under pressure of vagaries of weather conditions causing substantial loss. Attempts were made to rear the silkworm under indoor conditions during different seasons. In first attempt, the worms were reared from brushing till spinning and in second, worms were first reared under indoor conditions up to 2nd in star and then transferred to outdoor condition. Rearing performance, larval and cocoon parameters were compared with complete indoor and outdoor conditions. Throughout all the seasons, survival per cent of worms, effective rate of rearing, mature larval weight, cocoon weight, pupal weight and shell weight was significantly higher when the worms were reared for first two instars under indoor conditions compared to either complete indoor or outdoor rearing. The study suggests that, it is beneficial to rear muga silkworms inside up to second instar and then rear outside for reducing mortality of worms during chawki instars and for production of higher and good quality cocoons.